Unusual microwave response and bulk conductivity of very thin FeSe0.3Te0.7 films as a function of temperature - Barannik, A.A.; Cherpak, N.T.; Wu, Yun; Luo, Sheng; He, Yusheng; Kharchenko, M.S.; Porch, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
Results of X-band microwave surface impedance measurements of FeSe1–xTex very thin film are reported. The effective surface resistance shows appearance of peak at T ≤ Tc when plotted as a function of temperature. The authors suggests that the most well-reasoned explanation can be based on the idea of the changing orientation of the microwave magnetic field at a S–N phase transition near the surface of a very thin film. The magnetic penetration depth exhibits a power-law behavior of dlL(T) µ CTn, with an exponent n ≈ 2.4 at low temperatures, which is noticeably higher than in the published results on FeSe1–xTex single crystal. However the temperature dependence of the superfluid conductivity remains very different from the behavior described by the BCS theory. Experimental results are fitted very well by a two-gap model with D1/kTc = 0.43 and D2/kTc = 1.22, thus supporting s±-wave symmetry. The rapid increase of the quasiparticle scattering time is obtained from the microwave impedance measurements.